NMDA Receptor Opening and Closing-Transitions of a Molecular Machine Revealed by Molecular Dynamics - Černý, Jiří; Božíková, Paulína; Balík, Aleš; Marques, Sérgio M; Vyklický, Ladislav (Biomolecules, 2019)
We report the first complete description of the molecular mechanisms behind the transition of the N-methyl-d-aspartate (NMDA) receptor from the state where the transmembrane domain (TMD) and the ion channel are in the open configuration to the relaxed unliganded state where the channel is closed. Using an aggregate of nearly 1 µs of unbiased all-atom implicit membrane and solvent molecular dynamics (MD) simulations we identified distinct structural states of the NMDA receptor and revealed functionally important residues (GluN1/Glu522, GluN1/Arg695, and GluN2B/Asp786). The role of the "clamshell" motion of the ligand binding domain (LBD) lobes in the structural transition is supplemented by the observed structural similarity at the level of protein domains during the structural transition, combined with the overall large rearrangement necessary for the opening and closing of the receptor. The activated and open states of the receptor are structurally similar to the liganded crystal structure, while in the unliganded receptor the extracellular domains perform rearrangements leading to a clockwise rotation of up to 45 degrees around the longitudinal axis of the receptor, which closes the ion channel. The ligand-induced rotation of extracellular domains transferred by LBD-TMD linkers to the membrane-anchored ion channel is responsible for the opening and closing of the transmembrane ion channel, revealing the properties of NMDA receptor as a finely tuned molecular machine.
Keywords: glutamate receptor gating; NMDA receptor transition; Animals; molecular dynamics simulations; simulace molekulární dynamiky; krysa rodu Rattus; zvířata; receptory N-methyl-D-aspartátu; Molecular Dynamics Simulation; Receptors, N-Methyl-D-Aspartate; molecular modeling; open and closed state; Rats